PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN NASABAH PADA PT. MANDALA MULTI FINANCE CABANG PALU - DEWI, DEWI (Fakultas Ekonomi Universitas Tadulako, 2017)
The purpose of this study is to determine the effect of service quality on customer satisfaction at PT. Mandala Multi Finance Palu Branch. The sample used is 90 respondents, with sampling technique used is purposive sampling. Method of data analysis used in this research is Multiple Linear Regression. The results showed that service quality variables consisting of physical evidence, empathy, reliability, responsiveness, and collateral simultaneously have a significant effect on customer satisfaction at PT. Mandala Multi Finance Palu Branch. While the partial physical evidence, empathy, kahandalan, responsiveness, and guarantee also significantly affect customer satisfaction at PT. Mandala Multi Finance Palu Branch.